(untitled) (The Review of Diabetic Studies, 2025)
Background: The conceptualization of stress-related physical symptoms, including chronic musculoskeletal pain, tension-type disorders, and non-specific somatic complaints, necessitates a biopsychosocial approach. Conventional physiotherapy often focuses on biomechanical dysfunction, potentially overlooking the central role of the stress response and maladaptive neurocognitive processes in symptom perpetuation. Aim: This narrative review aims to critically synthesize contemporary evidence on the clinical application, proposed neurophysiological mechanisms, and therapeutic outcomes of MBP for the management of stress-related physical symptoms. Methods: A comprehensive literature search was conducted across PubMed, PsycINFO, CINAHL, and Scopus databases (2010-2024). Keywords included mindfulness, physiotherapy, physical therapy, somatization, psychosomatic, chronic pain, stress, and interoception. Results: The synthesized evidence indicates that MBP contributes to clinically meaningful reductions in pain intensity, disability, and psychological distress while improving pain acceptance and functional capacity. Key operative mechanisms appear to include the cultivation of interoceptive awareness, disruption of pain catastrophizing cycles, and downregulation of threat-system reactivity. MBP protocols typically integrate formal mindfulness practice with targeted movement education, promoting a decoupling of physical sensation from cognitive-emotional appraisal. Conclusion: MBP represents a robust, evidence-informed biopsychosocial framework that extends the scope of traditional physiotherapy. By systematically training attentional and regulatory capacities, MBP addresses core cognitive-affective drivers of stress-related symptomatology, offering a potent adjunct for managing complex, mind-body presentations.